An Lp-Estimate for Weak Solutions of Elliptic Equations. (25th June 2012) - Monsurrò, Sara; Transirico, Maria
Abstract : We prove an L p -a priori bound, p > 2, for solutions of second order linear elliptic partial differential equations in divergence form with discontinuous coefficients in unbounded domains.